Photography as Art : Art as Photography. - Maison Européenne de la Photographie, Chalon-sur-Saône; Fotoforum Kassel (Kassel : Fotoforum Kassel, 1975)
Anding, Volker ; Badura, Michael ; Bendkowski, Kazimierz ; Bobek, Ryszard ; Breier, Kilian ; Boltanski, Christian ; Camesi, Gianfredo ; Cieslewicz, Roman ; Cordier, Pierre ; Defraoui, Chérif ; Descamps, Bernard ; Dossi, Ugo ; etc.
Photography as Art : Art as Photography, Maison Européenne de la Photographie, Chalon-sur-Saône, 7. September - 12. Oktober 1975 / Fotoforum Kassel, 7. Januar - 8. Februar 1976
boek